Turn-taking practices in multi-party EFL oral proficiency tests. Issue 3 (13th September 2015) - Greer, Tim; Potter, Hitomi
Abstract : This study focuses on multi-party talk among EFL learners during peer-to-peer interaction in oral proficiency tests. We conduct a micro-analysis of the way test-takers in small groups use questions like 'How about you?' to manage turn-taking when speaking in rounds or through a pivot. We find that these deceptively simple questions have both an indexical referential element and an addressee-determining element that is used in conjunction with bodily conduct to select next-speaker, making them in fact a sophisticated interactional achievement. The study concludes by discussing how turn-taking practices in multi-party speaking tests can help make visible novice language users' orientations to learning.